Hubungan Persepsi Remaja Putri tentang Peran Orang Tua dengan Kesiapan Menghadapi Menstruasi Pertama (Menarche) di SMP Negeri 3 Palangka Raya - Chrisdianti Yulita (Jurnal Surya Medika (JSM), 2022)
The changes that happened when menarche come made adolescent girls felt confused, awkward, and uncomfortable. Some parents think that talking about menstruation is a taboo thing to do, as the result adolescent girl has less knowledge and attitude about physical and psychological changing related to menarche. Analyze the correlation between adolescent girls' perception of parents' role with the readiness toward menarche at SMPN 3 Palangka Raya. Quantitative research with cross-sectional design. Sampling technique using total sampling with 74 respondences adolescent girl VII grade students that have been got menarche. Primary data collection using a questionnaire as the instrument. Data analysis using the chi-square test (p=0,05) and correlation strength analysis using contingency coefficient (C). Adolescent girls' perception of parents' role is well enough perception as the result by 45 number respondents (60,8%), adolescents which are ready toward menarche by 40 respondents (54,1). Bivariate analysis shows that there is meaningly correlation between adolescent girls' perception of parents' role and their readiness toward menarche (p=0,002; contingency coefficient analysis C=0,386). There is a correlation between adolescent girls' perception of parents' role with the readiness toward menarche, by a weak correlation, parents have been giving contributions to the readiness of adolescents toward menarche, therefore hopefully adolescent girls can gain more knowledge about menarche.